Studi Tentang Hukum Air Dan Problematika Pemenuhan Hak Asasi Manusia Atas Air Di Indonesia - Chalid, Hamid (Jurnal Hukum & Pembangunan, 2018)
This research discusses the study on water law and the problematic of fulfillment of human rights to water in Indonesia. The focus of this research is to address the rights in accessing and obtaining water, as an essential prerequisite of human’s livelihood. This research also considers a case to describe the protection of the human right to water actualized in Indonesians daily life. The outcome of this research shows that there are dire problems and challenges in fulfilling human rights to water in Indonesia. Especially when faced with the global agenda of liberalizing and privatizing water, which often contradicts with the idea and efforts to protect human rights to water